Mediasi Penal di Indonesia - Usman Usman; Andi Najemi (Undang: Jurnal Hukum, 2018)
The settlement of criminal cases outside the court through mediation is a common phenomenon occurring in various regions of Indonesia. Penal mediation is done with the assumption that it can meet the justice and expediency, but what if viewed from the aspect of legality and legal certainty. This study aims to evaluate the settlement arrangement of penal proceeding through penal mediation and analyze the values ​​of justice, benefit and legal certainty in the settlement of criminal case through penal mediation. The study was conducted using normative/doctrinal legal research methods. This article concludes: 1) Settlement arrangement of criminal penalty through penal mediation is still limited to criminal case conducted by child. Although there are some provisions that provide for possible settlement of criminal cases outside the court, but not yet a penal mediation. Because it has not strictly regulated the mediation between the perpetrator and the victim, especially regarding the provision of compensation or compensation which is a means of diversion for the termination of prosecution and the imposition of a criminal. 2) The settlement of criminal cases through penal mediation can meet the values ​​of justice and benefit, but the limited regulation of penal mediation, the settlement of criminal cases through penal mediation is less reflect the value of legal certainty. Abstrak Penyelesaian perkara pidana di luar peradilan melalui mediasi merupakan fenomena yang umum terjadi di berbagai daerah di Indonesia. Mediasi penal dilakukan dengan anggapan dapat memenuhi tuntutan keadilan dan kemanfaatan, namun bagaimana jika dilihat dari aspek legalitas dan kepastian hukum. Penelitian ini bertujuan untuk mengevaluasi pengaturan penyelesaian perkara pidana melalui mediasi penal serta menganalisis nilai-nilai keadilan, kemanfaatan dan nilai kepastian hukum dalam penyelesaian perkara pidana melalui mediasi penal. Penelitian dilakukan dengan menggunakan metode penelitian hukum normatif atau doktrinal. Artikel ini menyimpulkan, 1) pengaturan penyelesaian perkara pidana melalui mediasi penal masih terbatas untuk perkara pidana yang dilakukan oleh anak. Meskipun beberapa ketentuan memberi kemungkinan adanya penyelesaian perkara pidana di luar pengadilan, ia belum merupakan mediasi penal; sebab belum mengatur secara tegas adanya mediasi antara pelaku dan korban, terutama terkait pemberian ganti rugi atau kompensasi yang merupakan sarana diversi untuk dihentikannya penuntutan maupun penjatuhan pidana. 2) Penyelesaian perkara pidana melalui mediasi penal dapat memenuhi nilai-nilai keadilan dan kemanfaatan, namun kurang mencerminkan nilai kepastian hukum disebabkan terbatasnya pengaturannya.